Suture self a book of medical cartoons - Cullum, Leo (Andrews McMeel Publishing, 2009)
No need for a second opinion--this collection is a healthy dose of funny.New Yorker cartoonist Leo Cullum found a different way to beat colon cancer: by creating cartoons that poked fun at the medical industry with his all-too-true medical-themed new work, Suture Self.With observations like "It was a rare, but serious, side effect" and "This IS a second opinion. At first, I thought you had something else." you will literally split your sides.This book should be in every doctor's office waiting room.Laughter is the best medicine. No copay required.* Includes over 100 medical-themed cartoons that will leave readers feeling great. This is a perfect get-well gift idea.* More than 800 of Leo's cartoons have appeared in The New Yorker since 1977.* Cullum's work has also appeared regularly in Barrons and the Harvard Business Review, and has been featured at the Brooklyn Museum of Art.